2017
DOI: 10.1007/s00294-017-0681-z
|View full text |Cite
|
Sign up to set email alerts
|

Transcription factor Afmac1 controls copper import machinery in Aspergillus fumigatus

Abstract: Copper (Cu) is an essential metal for all living organisms, although it is toxic in excess. Filamentous fungus must acquire copper from its environment for growth. Despite its essentiality for growth, the mechanisms that maintain copper homeostasis are not fully understood in filamentous fungus. To gain insights into copper homeostasis, we investigated the roles of a copper transcription factor Afmac1 in the life-threatening fungus Aspergillus fumigatus, a homolog of the yeast MAC1. We observed that the Afmac1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 46 publications
0
30
0
Order By: Relevance
“…The strain used in this study was A. fumigatus Af293. Potato dextrose agar (PDA; Difco, Detroit, USA), YG [ 27 ], and AMM [ 52 ] were regularly used for culturing the strain. To collect fresh conidia, the stored conidia were incubated on a PDA plate at 30 °C, or an AMM at 37 °C for 1 week.…”
Section: Methodsmentioning
confidence: 99%
“…The strain used in this study was A. fumigatus Af293. Potato dextrose agar (PDA; Difco, Detroit, USA), YG [ 27 ], and AMM [ 52 ] were regularly used for culturing the strain. To collect fresh conidia, the stored conidia were incubated on a PDA plate at 30 °C, or an AMM at 37 °C for 1 week.…”
Section: Methodsmentioning
confidence: 99%
“…Metal responsive transcription factors are able to sense the copper concentration within the cell and orchestrate a response by activating the copper import or copper detoxification, as required. These two regulatory paths are under the control of two separate transcription factors (Keller et al 2005) which were first discovered in S. cerevisiae as Mac1 and Ace1 (Balamurugan and Schaffner 2006), and later described in A. nidulans and A. fumigatus (Antsotegi-Uskola et al 2017;Cai et al 2019;Kusuya et al 2017;Wiemann et al 2017).…”
Section: Genetic Regulation Of Copper Homeostasismentioning
confidence: 99%
“…The N-terminal region contains a RGHR and GRP motifs and the BCu fist^domain, all together, they are responsible of the Cudependent DNA binding of the TF (Cai et al 2017). A Cterminal copper binding domain with two cysteine-rich motifs is responsible for copper sensing (Kusuya et al 2017). Sitedirected mutagenesis studies in A. fumigatus and A. nidulans have demonstrated that Cys residues of the N-terminal BCu fist^domain are essential for MacA DNA binding (Cai et al 2019).…”
Section: Genetic Regulation Of Copper Homeostasismentioning
confidence: 99%
See 1 more Smart Citation
“…As with other pathogenic microorganisms, metal homeostasis is closely related to the virulence of A. fumigatus [ 7 , 8 , 9 ]. In particular, copper has an important role in the growth of conidia [ 10 , 11 , 12 ], which directly affects the virulence of A. fumigatus , and the copper-responsive transcription factor AfMac1 is known to be directly related to the virulence of A. fumigatus [ 11 , 13 ].…”
Section: Introductionmentioning
confidence: 99%